Mengungkapkan Pengaruh Kesiapan Belajar Terhadap Kemampuan Berpikir Kritis Siswa di Sekolah Jsit Provinsi Lampung - Fahri, Ardian; Aman, Aman; Khoiriyah, Febriana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The development of science and the use of technology in learning encourage history learning to be able to adapt to the progress of education in the 21st century.  This study aims to determine the effect of learning readiness on critical thinking skills in students in schools under the guidance of the Integrated Islamic School Network (JSIT) in the Lampung province area. This study is a quantitative research with an Ex Post Facto Approach with a research sample of 194 students from all integrated Islamic schools in Lampung Province totaling six schools. The data in this study was collected through observation, interviews and the distribution of a questionnaire of 20 questions with the Likert Scale. The validity and reliability testing of the questionnaire was carried out by the Pearson Product Moment Correlation Test, the Cronbach' Alpha Test (α) and the assessment of instrument experts. The hypothesis test of this study was carried out using a Simple Linear Regression Test. The results in this study are at a significant level showing a value of 0.000 < 0.05, so it can be said that there is a positive and significant influence of Learning Readiness on students at the Integrated Islamic Network School in Lampung Province on Critical Thinking Ability by 21.5%. The test results show that the magnitude of the correlation value (R) is 0.462 in the output of the coefficient shows a constant value (a) of 23.256 and the Regression Coefficient value (b) is 0.430 so that it can be known that the regression equation is Y= 23.256 + 0.430X.